2005
DOI: 10.1042/bj20050630
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of heparan sulphate by hypochlorite: role of N-chloro derivatives and dichloramine-dependent fragmentation

Abstract: Activated phagocytes release the haem enzyme MPO (myeloperoxidase) and produce superoxide radicals and H2O2 via an oxidative burst. MPO uses H2O2 and Cl- to form HOCl, the physiological mixture of hypochlorous acid and its anion present at pH 7.4. As MPO binds to glycosaminoglycans, oxidation of extracellular matrix and cell surfaces by HOCl may be localized to these materials. However, the reactions of HOCl with glycosaminoglycans are poorly characterized. The GlcNAc (N-acetylglucosamine), GlcNSO3 (glucosamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
55
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 49 publications
13
55
0
Order By: Relevance
“…The presence of an additional absorbing species is seen at 270 nm consistent with that of heparin chloramide as found in a previous study at pH 7.4 [22]. The absorbances at 270 nm show a clear effect of pH with higher values being measured at the lower pHs as shown in Figure 2b.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The presence of an additional absorbing species is seen at 270 nm consistent with that of heparin chloramide as found in a previous study at pH 7.4 [22]. The absorbances at 270 nm show a clear effect of pH with higher values being measured at the lower pHs as shown in Figure 2b.…”
Section: Resultssupporting
confidence: 87%
“…Using the PAGE technique, similar site-specific reactions were also observed by Davies and co-workers for oxidation of several glycosaminoglycans by peroxynitrous acid, carbonate and hydroxyl radicals [19,20]. Equally significant for the understanding of potential molecular mechanisms involved in inflammation is the demonstration in these studies that hypochlorite species form chloramides when they react with amides [21] and in particular, with glycosaminoglycans [17,18,22]. Here, a substitution reaction occurs where the N-H group becomes an N-Cl group.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…In vitro studies of the reactions of hypochlorite with glycosoaminooglycans have indeed demonstrated that chloramides are produced in yields and rates of reaction which are dependent upon both pH and the ratio of hypochlorite to glycosaminoglycan concentrations [22,23] and have also shown that such derivatives may accelerate the fragmentation of glycosaminoglycans within the ECM [22]. Chloramides are weak oxidising agents and are therefore, potential biological targets for reducing radicals and other reducing agents.…”
Section: Introductionmentioning
confidence: 99%
“…Such derivatives may accelerate the fragmentation of glycosaminoglycans within the ECM [22]. Chloramides are weak oxidising agents and are therefore potential biological targets for reducing radicals and other reducing agents.…”
Section: Introductionmentioning
confidence: 99%